2000
DOI: 10.1080/019021400269934
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Erk2 by Respiratory Syncytial Virus in A549 Cells Is Linked to the Production of Interleukin 8

Abstract: The airway inflammation that results from respiratory syncytial virus infection is associated with a marked increase in interleukin 8 and neutrophils in the infected sites of the lung. In this study, the relationship between production of interleukin 8, infection of A549 cells by the virus, and activation of mitogen-activated protein kinases (MAPKs) was investigated. Infection of A549 cells by the virus caused an increase on the activity of extracellular signal-regulated kinase 2 (ERK2) by about 10-fold compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 36 publications
4
54
1
Order By: Relevance
“…The three major MAP kinase families are the ERK (1,2, 5, 7, and 8), p38 (␣, ␤, ␥, and ␦) and c-Jun N-terminal kinase (1, 2, and 3) (32,33). We have found a requirement for ERK activation in RSV-induced IL-8 production (8). More recently we have shown that ERK activation plays an important role in prolonged survival of RSV-infected airway epithelial cells (10).…”
Section: Respiratory Syncytial Virus (Rsv)mentioning
confidence: 95%
“…The three major MAP kinase families are the ERK (1,2, 5, 7, and 8), p38 (␣, ␤, ␥, and ␦) and c-Jun N-terminal kinase (1, 2, and 3) (32,33). We have found a requirement for ERK activation in RSV-induced IL-8 production (8). More recently we have shown that ERK activation plays an important role in prolonged survival of RSV-infected airway epithelial cells (10).…”
Section: Respiratory Syncytial Virus (Rsv)mentioning
confidence: 95%
“…Three major types of MAPK cascades have been reported in mammalian cells, namely the ERK1/ERK2 cascade, the JNK/stress-activated protein kinase cascade, and the p38 kinase pathway. The activity of the MEK, ERK and p38 kinase in RSV-infected epithelial cells has been linked to RSV replication, IL-8 release, and posttranscriptional RANTES gene expression, respectively (35,46,47). Moreover, it was reported that expression of TNF-␣ and IL-1␤ in RSV-infected epithelial cells required the activation of the p38 MAPK pathway (48).…”
Section: Discussionmentioning
confidence: 99%
“…For example, both adenovirus type 7 and respiratory syncytial virus induced IL-8 production through the activation of ERK in A549 cells (22,23), and the rhinovirus or TNF-␣ induced IL-8 production through the activation of p38 in BEAS-2B or rheumatoid fibroblast cells (24,25). IL-1 induced IL-8 production through the activation of JNK in KB epithelial cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activity of AP-1 has been reported to be regulated by MAPKs (22)(23)(24)(25)(26)(27). Therefore, vAtEpGS688-induced MAPK activation was examined.…”
Section: Vatepgs688 Activates Mapks and The Inhibitors And Dn Mutantsmentioning
confidence: 99%